Menelisik Keberhasilan Manajemen Kampanye: Uya Kuya Sebagai Caleg DPR RI Dapil DKI Jakarta II Pada Pemilu Legislatif Tahun 2024 - Ghaisani Putri, Almirah; Ghaitsa Majida, Iqlima; Ulfa Azis, Ardhana (Jurnal Ilmu Sosial dan Ilmu Politik, 2024)
This study aims to examine the success of Uya Kuya's campaign management as a candidate for the Indonesian House of Representatives (DPR RI) in the Jakarta II electoral district (Dapil) during the 2024 legislative elections. The problem addressed in this research relates to the limited understanding of effective campaign management strategies for increasing electability in highly competitive electoral districts, often referred to as 'hell districts'. Additionally, there is a need to evaluate the key factors influencing the success of political campaigns within the scope of legislative elections in Indonesia. The methodology employed is qualitative research with a literature review approach, involving descriptive data analysis from various secondary sources such as books, documents, and relevant articles. The research findings indicate that Uya Kuya's campaign management, including the recruitment of campaign teams, the determination of messages and media, as well as adaptive evaluations during the campaign, succeeded in increasing electability and winning the election in a highly competitive district.